Sphygmomanometer test to evaluate muscle strength in individuals with lower limb amputation: validity and reliability - Fabiana Amaral de Carvalho; Letícia Cristina Carvalho Silva; Regina Adriana Nogueira; Stella Maria Cândido Camargos; Andressa Silva; Viviane Santos Borges
Abstract Introduction: The sphygmomanometer test is an alternative and inexpensive method for assessment of muscle strength. This instrument was considered valid and reliable to measure the isometric strength in different health conditions, however, in individuals with limb amputations the properties of this instrument for this purpose, have not been investigated. Objective: To investigate the concurrent criterion validity, test-retest and inter-rater reliabilities of the aneroid sphygmomanometer test (AST) without modification, for assessment of the strength of subjects with lower limb amputations. Methods: Twenty-two subjects (57.6 ± 15.2 years) with lower limb amputations were included in this study. Maximum isometric force was assessed with a handheld dynamometer (microFet2®) and the AST. To identify differences between trials, one-way ANOVA was applied. To assess the concurrent criterion validity, test-retest and inter-rater reliabilities of the AST, Pearson's correlation coefficients of determination and intra-class correlation coefficient (ICC) were calculated. Results: For all muscle groups, no differences were observed between the trials (0.00001 ≤ F ≤ 0.10; 0.90 ≤ p ≤ 0.99). Significant, positive, and high to very high correlations were found between the HHD and the AST measures for the different numbers of trials for all assessed muscles (0.76 ≤ r ≤ 0.93; p ≤ 0.02). Test-retest (0.67 ≤ ICC ≤ 0.97) and inter-rater reliabilities (0.78 ≤ ICC ≤ 0.97) were adequate. The values obtained with the AST were good predictors of those obtained with HHD (0.58 ≤ r2 ≤ 0.85). Conclusion: For individuals with lower limb amputation, the AST showed adequate concurrent criterion validity, test-retest reliability and inter-rater reliability for the assessment of lower limbs muscle strength.